Bridging brain and blood: a prospective view on neuroimaging-exosome correlations in HIV-associated neurocognitive disorders - Luo, Haixia; Chen, Junzhuo; Liu, Jiaojiao; Wang, Wei; Hou, Chuanke; Jiang, Xingyuan; Ma, Juming; Xu, Fan; Aili, Xire; Zhou, Zhongkai; Li, Hongjun (Frontiers in Neurology, 2025)
HIV-associated neurocognitive disorder (HAND) is a complex neurological complication resulting from human immunodeficiency virus (HIV) infection, affecting about 50% of individuals with HIV and significantly diminishing their quality of life. HAND includes a variety of cognitive, motor, and behavioral disorders, severely impacting patients’ quality of life and social functioning. Although combination antiretroviral therapy (cART) has greatly improved the prognosis for HIV patients, the incidence of HAND remains high, underscoring the urgent need to better understand its pathological mechanisms and develop early diagnostic methods. This review highlights the latest advancements in neuroimaging and exosome biomarkers in HAND research. Neuroimaging, particularly magnetic resonance imaging (MRI), offers a non-invasive and repeatable method to monitor subtle changes in brain structure and function, potentially detecting early signs of HAND. Meanwhile, exosomes are nano-sized vesicles secreted by cells that serve as key mediators of intercellular communication, playing a crucial role in the neuropathology of HIV and potentially acting as a critical bridge between peripheral blood and central nervous system lesions. Thus, combining plasma exosome biomarkers with indicators derived from neuroimaging scans may enhance the early diagnosis of HAND. This review summarizes evidence supporting the role of exosomes as reliable biomarkers for early detection and management of HAND. Furthermore, we emphasize the correlation between neuroimaging biomarkers and exosome biomarkers and explore their potential combined use. This review discusses the technical challenges and methodological limitations of integrating these two types of biomarkers and proposes future research directions. This multidisciplinary integrative approach not only promises to improve the neurocognitive health management of HIV patients but may also offer valuable insights for research into other neurodegenerative diseases.